Four normative perspectives on public health policy-making and their preferences for bodies of evidence - Casper G. Schoemaker; Jeanne van Loon; Peter W. Achterberg; Frank R. J. den Hertog; Henk Hilderink; Johan Melse; Robert A. A. Vonk; Hans van Oers (BMC, 2020)
Abstract Calls for evidence-informed public health policy-making often ignore that there are multiple, and often competing, bodies of potentially relevant evidence to which policy-makers have recourse in identifying policy priorities and taking decisions. In this paper, we illustrate how policy frames may favour the use of specific bodies of evidence. For the sixth Dutch Public Health Status and Foresight report (2014), possible future trends in population health and healthcare expenditure were used as a starting point for a deliberative dialogue with stakeholders to identify and formulate the most important societal challenges for the Dutch health system. Working with these stakeholders, we expanded these societal challenges into four normative perspectives on public health. These perspectives can be regarded as policy frames. In each of the perspectives, a specific body of evidence is favoured and other types of evidence are neglected. Crucial outcomes in one body may be regarded as irrelevant from other perspectives. Consequently, the results of research from a single body of evidence may not be helpful in the policy-making processes because policy-makers need to account for trade-offs between all competing interests and values. To support these policy processes, researchers need to combine qualitative and quantitative methodologies to address different outcomes from the start of their studies. We feel it is time for the research community to re-politicise the idea of evidence use and for policy-makers to demand research that helps them to account for all health-related policy goals. This is a prerequisite for real evidence-informed policy-making.